Hak Waris pada Orang dengan Orientasi Gender Biner - Ahdah, Ina Tasya Aunil; Ahmad, Muh. Jufri (Journal Evidence Of Law, 2025)
Certain individuals experience gender identities that do not align strictly with being male or female. These individuals may identify as a blend of both male and female, as different genders at varying times, as having no gender at all, or as questioning the traditional binary understanding of gender. Terms commonly used to describe these identities include "genderqueer" and "non-binary." Such identities, which fall outside the conventional female-male framework, are gaining recognition in legal, medical, and psychological systems, largely due to the growing visibility and advocacy of this population. Population-based studies suggest that while the percentage of non-binary individuals is relatively small, the absolute number is significant. Despite their historical and global existence, non-binary genders remain marginalized. Consequently, individuals with these identities often face heightened risks of victimization, minority stress, and discrimination, although their identities are not inherently pathological or disordered. This paper examines the limited body of literature on this subject and explores how mental health professionals can better support clients with queer or non-binary gender identities and expressions. It discusses potential treatment approaches, along with their associated risks, to provide more informed and inclusive care.